Nanocellulose Reinforced Thermoplastic Starch (TPS), Polylactic Acid (PLA), and Polybutylene Succinate (PBS) for Food Packaging Applications - Nazrin, A.; Sapuan, S. M.; Zuhri, M. Y. M.; Ilyas, R. A.; Syafiq, R.; Sherwani, S. F. K. (Frontiers in Chemistry, 2020)
The common use of synthetic plastic is severely dangerous for our environment, because non-biodegradable plastic depletes natural resources. Nowadays, this plastic is very common for food packaging purpose. To overcome this problem, food packaging material should be substituted by green or environmental friendly materials, normally in the form natural fibre reinforced biopolymer composites. Thermoplastic starch (TPS), poly(lactic) acid (PLA) and poly(butylene succinate) (PBS) had been chosen for substitution, because of their availability, biodegradability and good food contact properties. Plasticizer (glycerol) was used to modify the starch under heating condition, which improved its processability. TPS films was sensitive to moisture and its mechanical properties were also not suitable for food packaging purpose. PLA and PBS have low oxygen barrier but good mechanical and processability. TPS, PLA and PBS need to be modified for food packaging requirement. Natural fibre was often incorporated into TPS, PLA, and PBS to overcome their weaknesses. The natural fibres were normally used in the forms of fibres, fillers, celluloses and nanocelluloses, but the focus of this paper is on nanocellulose. Nanocellulose reinforced polymers demonstrated an improvement in mechanical, barrier and thermal properties. The addition of compatibilizer as a coupling promoted fine dispersion of nanocelluloses in the polymer. Besides nanocellulose, TPS was also mixed with PLA and PBS because they are costly despite having commendable properties. Abundant, cheap and biodegradable caused the utilization of starch and natural fibre as filler.